1965
DOI: 10.1070/pu1965v008n03abeh003050
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Meteorites

Abstract: The objective of this work is to investigate the density of negative hydrogen ions in high-density, low-temperature recombining hydrogen plasmas. The recombining hydrogen plasmas were obtained in a compact divertor simulator excited by helicon-wave discharges. The electron density and the electron temperature of the recombining plasmas were (1-4) × 10 12 cm −3 and 0.1-0.2 eV, respectively, which were evaluated by comparing the population distribution of the excited states of atomic hydrogen with the Saha-Boltz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1967
1967
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…15 It was also presented that the concentration of carbon vacancies increases in samples grown with high growth rates. 16 It was reported that in sublimation growth of SiC with increasing growth rate, the Si/C ratio increases resulting in an increase of the C vacancies. 17 Furthermore, in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…15 It was also presented that the concentration of carbon vacancies increases in samples grown with high growth rates. 16 It was reported that in sublimation growth of SiC with increasing growth rate, the Si/C ratio increases resulting in an increase of the C vacancies. 17 Furthermore, in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…(26), where xG(x, Q 2 ) is the gluon distribution given by the Glauber formula (9). From (26), xG(x, Q 2 , b t ) can be written as…”
Section: 6mentioning
confidence: 99%
“…On the other hand, σ incl = N σ tot , where N is the average multiplicity and σ tot is the total cross section given by Eq. (9). N is equal to N P omeron N(one P omeron exchange), where N(one P omeron exchange) =…”
Section: 4mentioning
confidence: 99%
“…SC in the quark sector, calculated in the Eikonal approximation, were derived some time ago [14] [15] leading to an extensive phenomenology [16]. In our context we have…”
Section: Screening In the Quark Sectormentioning
confidence: 99%